Atomic spectrometry update: review of advances in the analysis of metals, chemicals and materials. Issue 11 (26th October 2020) - Carter, Simon; Clough, Robert; Fisher, Andy; Gibson, Bridget; Russell, Ben; Waack, Julia
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nanostructures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : This review has been modified somewhat compared with its predecessors in that the cultural heritage applications have been grouped together in their own section rather than being split between assorted other sections throughout the review. Hopefully, this will enable readers interested in that topic to locate all of the relevant papers more easily. There is no doubting that laser induced breakdown spectrometry (LIBS) is still the most rapidly expanding technique of interest for "industrial" samples. Its use for on-line or standoff analysis covers many topic areas including the metals production, scrap metal and plastic sorting industries, nuclear applications, in situ analysis of remote systems, e.g. power cable insulators, etc. It is also regarded as being minimally damaging to samples and has therefore found extensive use in the analysis of cultural heritage samples; especially when used in conjunction with chemometric tools to identify provenance or chronology. For the analysis of fuels, it was disappointing to see so many papers re-inventing the wheel, with numerous applications being published that offer little improvement on existing standard methods. In many cases, the protocols described were very lengthy or complicated and succeeded only in obtaining a similar result to an existing method, but with poorer precision and with no benefit to the end user. Other areas, e.g. catalysts has a huge amount of interest. However, the techniques used to characterise the materials are mature and often, many of the papers published do not discuss the analytical science in any detail. The analysis of pharmaceuticals and personal care products has had a large increase in research interest during this review period. This is potentially because of traditional methods, e.g. atomic absorption, slowly being replaced by more modern techniques, e.g. ICP-MS. Other growth areas of research have been the analysis of thin films, semiconductors and solar cells. Here, it is often X-ray-based analytical methods that are most commonly used, although some depth-profiling applications will use either LIBS or LA-ICP-MS. Another very popular area of research is that of nanoparticles. Here, the research focus has shifted from toxicological studies to the analysis of nanoparticles being used as carriers for drugs. This area is likely to increase further over the coming years. Consequently, analytical methods have also changed from using field flow fractionation to X-ray-based techniques such as XPS and XANES that describe the chemical composition of the particles rather than their size. Single particle ICP-MS for particle sizing is still an area of interest though.